Analisis Pelaksanaan Wakaf di Kuwait (ZISWAF: Jurnal Zakat dan Wakaf, 2019)
This Waqf in Kuwait is an endowment which is as old as the existence of Kuwaiti culture, the main purpose of this writing is to explore the implementation of waqf in Kuwait from the perspective of Endowments Jurisprudence by seeing the progress of waqf in Kuwait and with all its developments. The study method used in discussing this problem is literature research. The data in this study were obtained using the documentary method, to look for data on the implementation of waqf in Kuwait sourced from books, journals, the internet, and Papers. Kuwait has a strategy in developing waqf that is used effectively by developing waqf assets productively through various investment channels and distributing the results according to the conditions set by the waqif and making suitable waqf programs to improve the quality of existing Waqf Institutions so that Kuwait can progress and developed with effective waqf management and played an important role in the development of the Kuwaiti State.